Minimizing SIP Session Re-Setup Delay over Wireless Link in 3G Handover Scenarios. (30th May 2010) - Moon Moon, Bongkyo Bongkyo
Abstract : The delay in transmitting SIP messages over the wireless link for session resetup at handover is still major bottleneck for interactive multimedia service. In this paper, a proxy agent-based scheme is proposed to minimize the SIP session setup delay over a wireless link in 3G inter-subnet handover scenarios. This scheme is based on the two characteristics. One is that the major factor of SIP session re-setup delay is generally caused by the retransmissions in the unreliable wireless links, and the other is that most of the fields in request messages as well as response messages are duplicated when a set of SIP messages are exchanged during session re-setup procedure. In this scheme, no change is required in the SIP message processing except for the proxy agents in both BS and MH.